Factores que inciden en la intención emprendedora de los estudiantes de la facultad de Ciencias Administrativas de la Universidad Técnica de Cotopaxi. - Mena Jiménez, Claudia Katerine (2018)
The objective of the investigation project is to identify the relevant factors that affect the entrepreneurial intention of the students of the F.A.S at Technical University of Cotopaxi. The kind of descriptive and correlational research was used, through a binary logistic regression model (Logit), where the dependent variable is the entrepreneurial intention with two response options and the independent variables: sociodemographic, psychological and socioeconomic factors structured on a scale of Likert. To obtain the necessary information, a structured survey was applied to a sample of 280 undergraduate students in Commerce, Accounting and Executive Secretary. The results show that three variables influence the entrepreneurial intention and each factor obtained a statistically significant variable with a score lower than 0.050, these being the purpose after graduation, the motivation and the economic factor 1. It was evidenced by checking hypotheses that the null variables ho were rejected and three relevant independent variables were obtained, giving an association degree of Nagelkerke R squared of 12.60% which indicates that the proposed variables explain the model and 87.40% what that explain other types are not specified. It is concluded that the hypotheses proposed are not in accordance with the academic reality of the F.A.S students, because a relevant variable of each studied factor was obtained. Finally, An hypothesis is presented with the relevant variables on the entrepreneurial intention